CD11b Expression Level Measurement to Distinguish Asthma Phenotype in Pediatric Patients - Febriani, Tien Budi; Mahfudz, Soeroyo; Choironi, Emi Azmi; Devita, Ninda; Arjana, Adika Zhulhi; Imansyah, Muhammad Nur (Avicenna Journal of Medicine, 2025)
Background Inflammation is involved in asthma pathogenesis. Based on the majority of inflammatory cells found in blood samples, asthma is divided into neutrophilic and eosinophilic phenotype. CD11b is a leukocyte surface antigen that is involved in the inflammation process. However, the immunologic response mechanism in asthma phenotypes, especially in pediatric population, is still unclear. The aim of this study was to find the difference of CD11b expression in neutrophilic and eosinophilic phenotype of asthma in pediatric patients.Methods This is an analytic nonexperimental study. Data are gathered with cross-sectional method. Study subject is pediatric patients (5–17 years old) with asthma in Persaudaraaan Djamaah Hadji Indonesia and Wonosari hospitals. Blood samples for leukocyte differential count were obtained from patients who met the inclusion and exclusion criteria. Samples were analyzed with flow cytometry to measure the CD11b level. The obtained data was analyzed with independent t-test with Medcalc software.Result A total of 40 patients were enrolled in this study. Based on blood sample analysis, 70% patients had neutrophilic asthma and 30% patients had eosinophilic asthma. There was no significant difference between patient ages mean in both groups (7.071 vs. 7.471; p = 0.7186). The mean of leukocyte count was significantly higher in patients with neutrophilic asthma, compared with eosinophilic asthma (8.468 vs. 4.817 × 109/L; p = 0.0008). CD11b expression in neutrophilic asthma was significantly higher than eosinophilic asthma (p = 0.046). No association was found between CD11b expression levels with age, sex, and body mass index.Conclusion CD11b expression level is higher in neutrophilic phenotype compared with the eosinophilic phenotype in pediatric asthma patients. Its increased expression could provide insights into the mechanisms driving airway inflammation and remodeling. This marker might be explored as a target for novel therapies aimed at modulating immune activation to reduce asthma exacerbations and improve long-term outcomes.
Keywords: asthma phenotype; pediatric asthma; CD11b